Laparoscopic fundoplication after oesophageal atresia repair - Maria-Grazia Scarpa; Daniela Codrich; Miriam Duci; Damiana Olenik; Jürgen Schleef (Wolters Kluwer Medknow Publications, 2022)
Background: Esophageal atresia (EA) is a rare congenital malformation. A high incidence of GER unresponsive to medical management is noted with EA. Literature suggests that complications from GER can persist in adulthood. In paediatric age, laparoscopic treatment is a valid option even if recurrence rate is not negligible. Aims and Objectives: To evaluate our experience with gastro-esophageal reflux (GER) treatment after esophageal atresia (EA) repair. Materials and Methods: We retrospectively analysed 29 consecutive patients treated for EA at birth and studied for GER at our Institute in a period of 11 years. Results: 24/29 (82,7%) cases had symptoms of reflux, 17/29 (58,6%) cases were treated with laparoscopic fundoplication (LF). Three infants were younger than 6 months and had apparent life threatening events (ALTE) condition as principal indication for surgery. No intra-operative complications occurred. 3/17 LF had open surgical conversion due to technical problems. 2/17 cases required a second operation. At the last follow-up: (1) 6/17 (35,3%) of patients healed after the last operation, (2) 8/17 (47,1%) have GER improvement (four still in medical treatment), (3) 2/17 (11,8%) have persistent GER, (4) 1/17 (5,9%) died for causes not related to antireflux surgery. Conclusions: According to literature and to our retrospective analysis, LF for GER after EA repair is feasible, even if recurrence risk is not negligible. Infants less than 6 months old with associated conditions (malformations, gastrostomy/jejunostomy) seem to have a higher failure rate with a greater risk of conversion. Longer follow-up and multicenter experiences would guarantee an adequate surveillance for patients with EA.